Recent developments in Polyhydroxyalkanoates (PHAs) production – A review. (June 2020) - Sabapathy, Poorna Chandrika; Devaraj, Sabarinathan; Meixner, Katharina; Anburajan, Parthiban; Kathirvel, Preethi; Ravikumar, Yuvaraj; Zabed, Hossain M.; Qi, Xianghui
Highlights: Polyhydroxyalkanoates (PHAs) are inevitably a key biopolymer. Review focuses on the generation of PHA in an economically feasible way. Mixed Microbial Cultures (MMCs)- utilizing feedstocks from waste streams major parameters studied were discussed. Emphasis was given to the works carried out in the past decade and their coherence with the economical production of PHA. Challenges in the marketization and production of the biopolymer were also discussed. Abstract: Polyhydroxyalkanoates (PHAs) are inevitably a key biopolymer that has the potential to replace the conventional petrochemical based plastics that pose jeopardy to the environment globally. Even then the reach of PHA in the common market is so restricted. The economy of PHA is such that, even after several attempts the overall production cost seems to be high and this very factor surpasses PHAs usage when compared to the conventional polymers. The major focus of the review relies on the synthesis of PHA from Mixed Microbial Cultures (MMCs), through a 3-stage process most probably utilizing feedstocks from waste streams or models that mimic them. Emphasis was given to the works carried out in the past decade and their coherence with each and every individual criteria (Aeration, Substrate and bioprocess parameters) such that to understand their effect in enhancing the overall production of PHA.